2008
DOI: 10.1177/147323000803600611
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Atorvastatin Therapy to Decrease the Systemic Inflammatory Response after Coronary Artery Bypass Grafting

Abstract: The effect of pre-operative atorvastatin on systemic inflammatory response syndrome (SIRS), often seen after coronary artery bypass grafting (CABG) was evaluated in 40 patients undergoing elective CABG. Patients were divided into two groups: group I (pre-operative LDL cholesterol > or = 100 mg/dl; n = 20) received 20 mg/day atorvastatin for at least 15 days pre-operatively; group II (pre-operative LDL cholesterol < 100 mg/dl; n = 20) did not receive antihyperlipidaemic agents. All patients underwent CABG with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Patients treated with statins prior to surgery have been shown to have a blunted systemic inflammatory response 57,58 and reduced amounts of cellular adhesion molecules, 59 which could confer acute protective effects in grafted vessels. 60,61 As seen in patients with ACS, statins have been shown to increase the levels of endothelial progenitor cells in CABG patients, 62 allowing for the rapid repair of damaged vasculature.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…Patients treated with statins prior to surgery have been shown to have a blunted systemic inflammatory response 57,58 and reduced amounts of cellular adhesion molecules, 59 which could confer acute protective effects in grafted vessels. 60,61 As seen in patients with ACS, statins have been shown to increase the levels of endothelial progenitor cells in CABG patients, 62 allowing for the rapid repair of damaged vasculature.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…There is however increasing evidence to suggest that statins may be an effective preventative therapy. Statins possess anti-oxidant properties (5), improve endothelial function (6) and decrease inflammation (7-9). Several animal studies have shown that statins are reno-protective when given prior to an ischemia-reperfusion type injury (5-8).…”
Section: Introductionmentioning
confidence: 99%
“…[94][95][96][97][98] Administering statins before surgery has been shown to diminish the systemic inflammatory response associated with the use of cardiopulmonary bypass during CABG. [99][100][101][102] Through antisympathetic activity and the stabilization of ion channels, 103 both randomized and observational studies have illustrated that statin treatment significantly reduces the risk of AF after CABG both in the perioperative period and long term after surgery. [104][105][106][107][108][109][110] Although selection bias cannot be excluded, several nonrandomized, retrospective studies have noted significant associations between perioperative statin use and a lower risk of postoperative renal dysfunction, 111,112 infection, 113 stroke, [114][115][116] and mortality, 111,[116][117][118] even among patients without elevated lipid profiles before surgery.…”
Section: Antithrombotic Therapymentioning
confidence: 99%